-أثر العدالة التنظيمية على سلوك المواطنة في المنظمة دراسة حالة في الشركة الوطنية لتوزيع الكهرباء والغاز-الأغواط - بركانة تركية; رقارقي صفية; بعاج الهاشمي (جامعة عمار ثليجي الاغواط, 2021)
This study aimed to identify the impact of the dimensions of rganizational justice on the behavior of citizenship in the National Institution for the Distribution of Sonelgaz in the state of Laghouat, using the descriptive analytical method, and using a sample estimated at (65) workers from the study population of (475) workers of all ranks, depending on the questionnaire. After the data was treated with the help of (SPSS, SMART PLS, Excel 2010) using appropriate statistical methods, the following most important results were reached -There is a statistically significant effect at the level of significance (α≤0.05) for both dimensions of transactional justice and procedural justice on the citizenship behavior in the institution, while there is no statistically significant effect at the level of significance (α≤0.05) between distributive justice and sympathy behavior in the institution . -The average level of workers' awareness of organizational justice was average. -The average level of workers' sense of citizenship behavior was acceptable. The recommendations were as follows Enhancing the two dimensions of transactional and procedural justice because they affect the behavior of citizenship in the institution. The necessity of paying attention to distributive justice, by taking into account the effort and pressures that workers experience within the institution, with the need to encourage initiatives that lead to improving work.